Community Science in Support of Ecosystem-Based Management: A Case Study from the Damariscotta River Estuary, Maine, USA - Risley, Sarah; Pellowe, Kara; Britsch, Melissa; White, Meredith; Leslie, Heather (Maine Policy Review, 2023)
Coastal marine ecosystems are dynamic social-ecological systems (SESs) that support diverse ecosystem services and human activities. The complexity of SESs means that ecosystem-based approaches are increasingly used to support coastal marine ecosystem stewardship. We report how a community science program in Maine, USA offers a model of organizational innovation to expand capacities for shellfish research and management. Since 2019, we have collaborated with local students, shellfish harvesters, and others in data collection, interpretation, and application, contributing to local shellfish management and ecosystem sustainability. We demonstrate how community-based social and ecological research can build adaptive capacities by centering local knowledge; generating long-term and fine-scale datasets; supporting community-led management and civic engagement; and contributing to field methods that people with varied lived experiences and training can implement in a sustainable fashion. Our approach can be adapted to other contexts, particularly in data-limited SESs that are experiencing observable social and ecological change.